O193 ROLE OF MALNUTRITION IN 0ESOPHAGEAL SURGERY FOR CANCER. (23rd November 2019) - Alfieri, R; Nardi, M; Moretto, V; Pinto, E; Briarava, M; Pomba, L; Scarpa, M; Pilati, P L; Castoro, C
Abstract: Aim: To investigate whether preoperative malnutrition is associated with long term outcome and survival in patients undergoing radical oesophagectomy for oesophageal or oesophagogastric junction cancer. Background & Methods: Dysphagia, weight loss, chemo-radiationtherapy frequently lead to malnutrition in patients with oesophageal or oesophagogastric junction cancer. Severe malnutrition is associated with higher risk of postoperative complications but little is known on the correlation with long term survival. We conducted a single center retrospective study on a prospectively collected database of patients undergoing oesophagectomy from 2008 and 2012 in order to evaluate the impact of preoperative malnutrition with postoperative outcome and long term survival. Preoperative malnutrition was classified as: prealbumin level less than 220 mg/dL (PL), MUST index (Malnutrition Universal Screeening Tool) >2 and weight loss >10%. Results: 177 consecutive patients were considered: due to incomplete data 60 were excluded from the analysis that was performed on 117 patients. PL was reported in 52 (44%) patients, MUST index was recorded in 62 (53%), 58 (49%) patients presented more than 10% weight loss at the preoperative evaluation. PL was associated with more postoperative Clavien-Dindo 1-2 complications (p=0.048, OR 2.35 95%IC 1.001-5.50), no differences were observed in mortality, anastomotic leak, major pulmonary complications. MUST index was not correlated with postoperative complications nor mortality but resulted worse in patients treated with chemo-radiotherapy (p=0.046, OR 1.92 95%CI 1.011-3.64). Weight loss >10% was not associated with postoperative complications or mortality. Overall 7 years survival rate was 69%. and DFS was 68%. Malnourished patients did not differ from non-malnourished regarding age, sex, tumor site, tumor stage and histology. No significant difference in 7 years survival rates was observed in patients with PL <220 mg/dL ( 55 % vs 67%), neither in patients with MUST score>2 (58% vs 72%), nor in patients with weight loss >10% (53% vs 70%). Conclusions: Malnutrition is more common in patients treated with chemoradiation therapy and it is associated with postoperative complications. However, both long term and disease free survival are not affected by preoperative nutritional status. Larger patient population and data on long term postoperative nutritional status will be analyzed in further studies.